Fabricated AZO on dual-stacked patch transparent antenna / Robiatun A. Awang … [et al.] - A. Awang, Robiatun; Mamat, Mohamad Hafiz; Awalludin, Mardhiah; Ali, Mohd Tarmizi (Universiti Teknologi MARA, 2019)
The development of a simple dual-stacked transparent patch antenna operating at 5 GHz is presented. A transparent conducting oxide material known as aluminum doped Zinc Oxide (AZO) for radiating patch and a transparent perspex acrylic for supporting substrate are used in this antenna design. The AZO thin film thickness of 200 nm has been deposited on the Perspex using RF magnetron sputtering technique. Employing an air gap in the antenna structure is proven to exhibit wider bandwidth compared to the single patch structure transparent antenna. The dual-stacked antenna is fabricated and measured to validate the simulation results. A measured return loss was slightly shifted to the lower frequency The proposed transparent material has the potential to be implementing in any transparent devices